Peran Materi Etika Tata Krama Muslim dalam Kitab Nisaiyah Terhadap Karakter Jujur Santri di Pondok Pesantren Miftahul Huda Rancabungur Bogor - Mida Mudiatul Millah; Yunizul Pesha, Indry Nirma; Sinta Dewi, Reni (Economic Reviews Journal, 2024)
The problembehind this research is the moral crisis that is rife in society, while one of the evidences of the moral crisis in the Miftahul Huda Islamic boarding school, Rancabungur Bogor is that out of 100% of the number of students there are 30% of students who still use goods that do not belong to them. The objectives of this study are (1) to find out the ethics of manners of students at the Miftahul Huda Islamic Boarding School Rancabungur Bogor, (2) to find out the honest character of students at the Miftahul Huda Islamic Boarding School Rancabungur Bogor, (3) to find out of thinking significant the role of muslim etiquette ethics material of nisaiyah book on the honest character of students at the Miftahul Huda Islamic Boarding School Rancabungur Bogor. The discussion of thinking between variable X (manners ethics) and variable Y (honest character) which aims to find a mature concept that is used to explain every problem in ths study. This study uses a survey method with a quantitative approach where the data collection process is carried out by distributing research questionnaries about the material on muslim ethics and honest character that is being disseminated to 31 students (1) the ethics of students manners obtained an average value of 61, 48 these results indicate that it is categorized as good, (2) that honest characters of the students obtained an average score of 62, 83 that results indicate that it is categorized as good, (3) the results of the simple linear regression test 0,036< 0,05 show that there is a positive significant the role of muslim etiquette ethics material of nisaiyah book on the honest character of students at the Miftahul Huda Islamic Boarding School Rancabungur Bogor. Thus the material on muslim etiquette in the nisaiyah book on the honest character of students at the Miftahul Huda Islamic Boarding School Rancabungur Bogor can play a role.